2015
DOI: 10.1007/s11356-015-5102-6
|View full text |Cite
|
Sign up to set email alerts
|

Emission factor and balance of mercury in fish farms in an artificial reservoir in NE Brazil

Abstract: This paper estimated the mercury (Hg), emission factor, and mass balance from caged fish farming in the Castanhão Reservoir, NE Brazil, based on monitoring of a typical farm of Nile tilapia (Oreochromis niloticus). The total Hg input to the farm reached 1.45 gHg ha(-1) year(-1), from which 0.21 gHg ha(-1) year(-1) was exported out as fish biomass, ultimately resulting in an emission factor of 1.24 gHg ha(-1) year(-1) for the reservoir or approximately 8.27 mgHg ton fish(-1) year(-1) produced. Most of the input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…After, however, differences between surface and bottom water temperatures were well below 1.0°C. At the Castanhão reservoir, the monitoring of current velocities and directions obtained through the deployment of an ADCP Oliveira et al 2015) showed the highest current velocities at the surface and a decrease towards the reservoir bed. This supports the relatively small remobilization of bottom sediment and the permanence of the water column stratification.…”
Section: Hydrological Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…After, however, differences between surface and bottom water temperatures were well below 1.0°C. At the Castanhão reservoir, the monitoring of current velocities and directions obtained through the deployment of an ADCP Oliveira et al 2015) showed the highest current velocities at the surface and a decrease towards the reservoir bed. This supports the relatively small remobilization of bottom sediment and the permanence of the water column stratification.…”
Section: Hydrological Settingmentioning
confidence: 99%
“…During the 2010-2014 period, total tilapia production from the Castanhão reservoir averaged 18,000 tons per year, but considering the total potentially available area on the reservoir legally able to harbor fish cages, production figures could reach 40,000 tons per year. A major environmental aspect of intensive fish aquaculture practiced in the Castanhão reservoir is the intensive use of aquafeed to sustain high production figures of about 150 t.ha -1 .yr -1 ; to reach such a production, with a conversion rate of 1.7, about 258 t.ha -1 .yr -1 of aquafeeds are necessary (Oliveira et al 2015). Excess aquafeeds and fish excreta result in this activity displaying the largest emission factors for nitrogen and mercury and the second largest for phosphorus, among all anthropogenic sources emitting these substances to the Castanhão reservoir (Table III).…”
Section: The Impact Of Fish Farmingmentioning
confidence: 99%
See 2 more Smart Citations
“…Molisani et al (2015) reported, based on stable C and N distribution, current velocities and deposition rates of fecal pellets, that effluents from cage aquaculture (feed and feces) were not extensively reaching the water column and the bottom sediments of the cage area, on the contrary, effluents from farms are carried out to the deeper, central region of the reservoir. Hydrodynamic modeling of the reservoir (Molisani et al, 2015;Oliveira et al, 2015) showed surface wind-drive currents to move westwards from the center deeper part of the reservoir to shore, whereas bottom currents flush-out fish farm areas and incoming runoff eastwards to the deeper regions (Group 1 region), where stratification exists during high volume periods (e.g., in station 6 in November, 2011 -Supplementary Tab. 1), but is broken when the reservoir volume decreases.…”
Section: Discussionmentioning
confidence: 99%